2019
DOI: 10.4103/ipj.ipj_8_19
|View full text |Cite
|
Sign up to set email alerts
|

Risperidone-induced retrograde ejaculation and lurasidone may be the alternative

Abstract: Medication adherence with antipsychotics is adversely impacted by the burden of untoward adverse effects. In particular, sexual side effects are often underreported by patients, which may interfere with drug compliance. Presented here is the case of a 35-year-old male with schizophrenia, previously treated with risperidone following which he developed sexual dysfunction and hence was stopped. He was admitted to our psychiatric inpatient ward after a second psychotic exacerbation of the disorder after being dru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 7 publications
0
4
0
Order By: Relevance
“…Risperidone has been associated with other problems in addition to regular sexual dysfunction, like retrograde ejaculation and urinary dysfunctions [ 90 , 91 , 92 , 93 , 94 ]; anejaculation [ 95 , 96 ]; and, on rare occasions, hypersexuality [ 97 , 98 ]. Part of this SD could be related to high levels of blood prolactin [ 84 , 99 ], resulting in complex hormone regulations that decrease testosterone [ 100 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Risperidone has been associated with other problems in addition to regular sexual dysfunction, like retrograde ejaculation and urinary dysfunctions [ 90 , 91 , 92 , 93 , 94 ]; anejaculation [ 95 , 96 ]; and, on rare occasions, hypersexuality [ 97 , 98 ]. Part of this SD could be related to high levels of blood prolactin [ 84 , 99 ], resulting in complex hormone regulations that decrease testosterone [ 100 ].…”
Section: Resultsmentioning
confidence: 99%
“…Further less-researched options include ziprasidone, with a 3-month prospective switching study showing improvement in SD [ 113 ]. Lurasidone, with a case report showing a decrease in SD when switching from risperidone [ 90 ] and a clinical trial showing it was not associated with treatment-related SD versus placebo [ 164 ], could be a useful alternative. Nonetheless, hypersexuality has been associated with both lurasidone [ 165 ] and ziprasidone [ 166 ], so additional research is needed.…”
Section: Resultsmentioning
confidence: 99%
“…A detailed look at the anatomy of the fallopian tube, a 7-9 cm elongated structure resembling a trumpet, emphasizes its pivotal role in reproduction. From the cornual attachment to the uterine cavity to the fimbriated end that curves over the ovary, the fallopian tube facilitates the journey of the ovulated egg, where fertilization takes place [ 12 ].…”
Section: Discussionmentioning
confidence: 99%
“…These interactions may suggest lurasidone’s better tolerability profile and reduced sexual side effects compared to risperidone. One case study also showed a decrease in sexual dysfunction when switching to lurasidone from risperidone [ 12 ]. However, more research must be done to corroborate these findings, and we hope this case study adds to the body of literature in the area.…”
Section: Discussionmentioning
confidence: 99%